2020
DOI: 10.1007/s00702-020-02289-6
|View full text |Cite
|
Sign up to set email alerts
|

Altered urinary tetrahydroisoquinoline derivatives in patients with Tourette syndrome: reflection of dopaminergic hyperactivity?

Abstract: Tetrahydroisoquinolines (TIQs) such as salsolinol (SAL), norsalsolinol (NSAL) and their methylated derivatives N-methyl-norsalsolinol (NMNSAL) and N-methyl-salsolinol (NMSAL), modulate dopaminergic neurotransmission and metabolism in the central nervous system. Dopaminergic neurotransmission is thought to play an important role in the pathophysiology of chronic tic disorders, such as Tourette syndrome (TS). Therefore, the urinary concentrations of these TIQ derivatives were measured in patients with TS and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…8 On the other hand, increased levels of isoquinoline derivatives present following alcohol consumption, such as SAL, 49 due to acetaldehyde production needed for their synthesis, are not associated with an increased risk of PD development. 50 What is more, higher urinary concentrations of SAL and NMSAL were found in Tourette syndrome and Tourette syndrome with ADHD patients (yet not de novo) 51 as well as in adolescents with ADHD only 52 compared with healthy controls. Thus, such increased levels of SAL and its derivatives might be a consequence of impaired dopaminergic pathways but not an underlying and direct cause of neurodegeneration.…”
Section: ■ Discussionmentioning
confidence: 99%
“…8 On the other hand, increased levels of isoquinoline derivatives present following alcohol consumption, such as SAL, 49 due to acetaldehyde production needed for their synthesis, are not associated with an increased risk of PD development. 50 What is more, higher urinary concentrations of SAL and NMSAL were found in Tourette syndrome and Tourette syndrome with ADHD patients (yet not de novo) 51 as well as in adolescents with ADHD only 52 compared with healthy controls. Thus, such increased levels of SAL and its derivatives might be a consequence of impaired dopaminergic pathways but not an underlying and direct cause of neurodegeneration.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Norsalsolinol (NSAL) regulates the transmission and metabolism of DA in the CNS in vivo. A case–control study reported by Capetian P in 2021 showed that the urinary concentrations of NSAL were significantly increased in patients with TS, indicating that dopaminergic hyperactivity is involved in the pathophysiology of TS [ 15 ]. In a study assessing changes in DA in TS patients by positron emission tomography (PET), Steeves and colleagues showed that, after deep brain stimulation, the clinical improvement was related to decreased DA release and upregulation of DA receptors [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dopaminergic neurotransmission and its metabolism in the central nervous system of non-medicated patients with TD ( n = 7), TD + ADHD ( n = 12), and healthy controls ( n = 19) was recently investigated by Capetian et al [ 49 ]. They determined Tetrahydroisoquinolines (TIQs; modulating dopamine and thus giving another perspective on monoaminergic dysfunction [ 67 ]) in the urine by a two-phase chromatographic approach.…”
Section: Level “Abnormal Brain Conditions”mentioning
confidence: 99%